CUSTOMER LOYALTY IN INDONESIAN SHARIA BANKS: INTEGRATING FINANCIAL ASPECTS, FINTECH APPLICATIONS, AND THE CARTER MODEL - Muhammad, Helmi; Sari, Niki Puspita (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
As a competitive strategy, Bank Syariah Indonesia (BSI) is interested in emphasizing service quality, with a focus on customer loyalty and referral. The CARTER model is becoming increasingly popular among researchers as a tool for evaluating the quality of services provided by Islamic banks. This study seeks to investigate the effects of financial aspects, FinTech use, and CARTER model dimensions on BSI customer loyalty. The study included all customers of BSI Malang across three areas: Malang City, Batu City, and Malang Regency, with a sample size of 100 respondents. The data were analyzed using multiple linear regression. The findings indicate that the financial aspects, FinTech use, and CARTER model dimensions have a significant effect on BSI customer loyalty. Compliance (adherence to Sharia principles) was the most important factor in the CARTER dimension, followed by assurance, reliability, empathy, and responsiveness. Although the financial aspects and tangibility are considered part of the service quality dimension, they do not significantly contribute to BSI customer loyalty. In addition to cultivating technical skills in its workforce, BSI relies on the practical implications of Sharia compliance to enhance its competitive strategy.